Successful approaches to placing and supporting apprentices and trainees with disability in Australia - Lewis, G.; Thoresen, Stian; Cocks, Errol (IOS Press, 2011)
This paper presents an amalgamation of three sequential research projects conducted by EDGE Employment Solutions over the past decade. The first project, commenced in 1999, was a local initiative to increase the number of apprentices and trainees with disability being supported by EDGE. The completion rate for participants in this project was equivalent to that of people without disability undertaking apprenticeships and traineeships in Australia. However, it was found that Group Training Organisations, who hire apprentices and trainees to then place them with different employers, did not have the necessary skills or resources to place and support people with disability. To fill this gap, the second research project, undertaken in 2002, surveyed all 180 Group Training Organisations operating in Australia. This was followed by a site visit of six GTOs who were most successful in their disability efforts, to discern best practice in placing and supporting apprentices and trainees with disability. The third research project, which built on the findings of the previous two projects, was initiated in 2003 and enlisted 20 Group Training Organisations and 20 Disability Employment Services from around Australia to form partnerships to capitalise on their complementary expertise and resources. Apprenticeship and traineeship completion rates for participants in the third project surpassed those for people without disability in Australia. This paper presents and discusses the successful strategies researched and developed through these three projects.